Gravitational waves in Brans-Dicke theory with a cosmological constant - DELİCE, ÖZGÜR (SPRINGER, 2021)
Weak field gravitational wave solutions are investigated in Brans-Dicke (BD) theory in the presence of a cosmological constant. In this setting the background geometry is not flat but asymptotically de-Sitter. We investigate the linearised field equations, and their gravitational wave solutions in a certain gauge choice. We will show that this theory leads to massless scalar waves as in original BD theory and in contrast to massive BD theory. The effects of these waves on free particles and their polarization properties are studied extensively and effects of the cosmological constant is analyzed in these phenomena in detail. The energy flux of these waves are also discussed in this background. By analyzing this flux, we obtain a critical distance where the waves cannot propagate further, which extends Cosmic no Hair Conjecture (CNC) to BD theory with a cosmological constant.
Keywords: MODIFIED GRAVITY; RELATIVISTIC THEORY; MACHS PRINCIPLE; HIGH-FREQUENCY; RENORMALIZATION; UNIVERSES; RADIATION; LIMIT; FIELD